Prenatal care and obstetric complications at a Family Health Center in Goiânia, Goiás (Research, Society and Development, 2023)
The objective of this study was to evaluate the sociodemographic profile and the quality of prenatal care offered to pregnant women attended at a Family Health Center and to verify the association between adequate prenatal care and possible pregnancy complications. It is a cross-sectional study carried out at the SUS prenatal service in the city of Goiânia, Goiás from January 2021 to July 2022. Data were collected from electronic medical records from February 2022 to July 2022. The variables were sociodemographic, related to the coverage and quality of prenatal care and pregnancy and the pregnant woman's health history. The x² test was applied to assess the association between obstetric complications and other variables. 157 medical records were analyzed. Most pregnant women were 21-34 years old (62.4%), had completed high school (47.1%) and were married (39.5%). Only 38.9% of pregnant women had ≥ 6 consultations. 75.8% had their first consultation in the first quarter. 45.1% underwent at least two ultrasounds. Only 24.8% performed two phases of the Mom's Test. Less than half had access to adequate or more than adequate prenatal care (38.9%). Regarding obstetric complications, 58.6% of the pregnant women had them, with urinary tract infection (29.9%) being the main one. There was an association between complications and not having a consultation in the first trimester (p=0.0482), in addition to having none or only one Mother's Test (p=0.0463). All pregnant women with a history of STIs also had complications (p=0.0172). Thus, improvements need to be made so that prenatal care fulfills its protective role.